2006
DOI: 10.1002/nbm.1003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance angiography of collateral vessel growth in a rabbit femoral artery ligation model

Abstract: Collateral vessel growth was visualized in a rabbit femoral artery ligation model by serial contrast-enhanced magnetic resonance angiography (MRA) at 1.5 T in comparison with X-ray angiography (XRA). XRA and MRA were performed directly after femoral artery ligation (day 0+) and after 7 and 21 days. XRA (in-plane resolution, 0.3x0.3 mm) was performed with arterial catheterization for fast injection of iodinated contrast agent just proximal to the aortic bifurcation. MRA (in-plane, 0.6x0.6 mm) was performed at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
3
18
1
Order By: Relevance
“…The fact that these pathways are the first to provide casting material to the distal vasculature suggests that they are the pathways of least resistance and represent the dominant or primary collaterals. These are the vessels that others have concluded are primarily responsible for distal limb perfusion (22,56). This is similar to the clinical situation as the major collaterals in the lower extremity are identified as preexisting named arteries (23, 29 -31, 57).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The fact that these pathways are the first to provide casting material to the distal vasculature suggests that they are the pathways of least resistance and represent the dominant or primary collaterals. These are the vessels that others have concluded are primarily responsible for distal limb perfusion (22,56). This is similar to the clinical situation as the major collaterals in the lower extremity are identified as preexisting named arteries (23, 29 -31, 57).…”
Section: Discussionsupporting
confidence: 60%
“…The largest of the preexisting vessels are typically those that become the dominant collaterals (35,45,51). Combined anatomic and modeling studies have predicted that hindlimb flow subsequent to femoral artery occlusion is primarily determined by these collaterals (22,56). This is consistent with studies of segmental resistances that demonstrated that compensation in the collateral vessels is of significantly greater hemodynamic importance than adaptations in the distal microvasculature (43,71,75).…”
supporting
confidence: 56%
“…We introduced the technique of serially obtained in vivo angiograms (27). Both number and lumen of collaterals were increased directly after ligation up to 21 days after ligation in control rabbits, but this process was significantly impaired in diabetic rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…The rabbit ischemic hind limb model has been used extensively in arteriogenesis research. In recent years, we have adapted this model to study collateral artery growth longitudinally in the same animal (27). The aim of the present study was to investigate the effect of experimental diabetes on both the acute and remodeling phases of collateral development in the ischemia hind limb model and the role of monocyte chemotaxis.…”
mentioning
confidence: 99%
“…The development of collateral arteries can be monitored non-invasively by serial MR angiography (MRA) (22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%